2018
DOI: 10.1097/tp.0000000000001966
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human CD200 Overexpression in Pig-to-Human Xenogeneic Immune Response Compared With Human CD47 Overexpression

Abstract: Therefore, overexpression of human CD200 in donor pigs could constitute a promising strategy for overcoming xenograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…In vitro, expression of hCD47 on pig cells not only suppresses the activation of human macrophages but, importantly, also suppresses inflammatory cytokine (TNF‐α, IL‐1β, IL‐6) production, and macrophage‐mediated pig cell cytotoxicity . In addition, Yan et al have demonstrated that pig graft infiltration by human T cells is suppressed by expression of hCD47 .…”
Section: Expression Of Hcd47mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, expression of hCD47 on pig cells not only suppresses the activation of human macrophages but, importantly, also suppresses inflammatory cytokine (TNF‐α, IL‐1β, IL‐6) production, and macrophage‐mediated pig cell cytotoxicity . In addition, Yan et al have demonstrated that pig graft infiltration by human T cells is suppressed by expression of hCD47 .…”
Section: Expression Of Hcd47mentioning
confidence: 99%
“…In vitro, expression of hCD47 on pig cells not only suppresses the activation of human macrophages but, importantly, also suppresses inflammatory cytokine (TNF‐α, IL‐1β, IL‐6) production, and macrophage‐mediated pig cell cytotoxicity . In addition, Yan et al have demonstrated that pig graft infiltration by human T cells is suppressed by expression of hCD47 . Illustrating the complex interaction of the immune, coagulation, and inflammatory systems, when hCD47 was expressed with human tissue factor pathway inhibitor (hTFPI), hCD47‐SIRP‐α signaling was potentiated …”
Section: Expression Of Hcd47mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, porcine cells expressing hCD47 can reduce their phagocytosis by human macrophages (62). Moreover, the expression of hCD47 in porcine endothelial cells not only suppressed macrophage-mediated cytotoxic activity and inflammatory cytokine (TNF-α, IL-1β, IL-6) production but also inhibited human T-cell infiltration (133). In vivo, hCD47 expression increased xenogeneic hematopoietic engraftment chimerism in the murine model (102) and prolonged the survival porcine skin grafts in baboons (134).…”
Section: Inhibition Of Cellular Xenograft Rejectionmentioning
confidence: 99%
“…Results found in one study showed that porcine CD47 was able to bind to human SIRPA in vitro, while another showed that phagocytic inhibition was not induced between human macrophages and pig cells . Expression of human CD47 on porcine cells was required to inhibit phagocytosis by human macrophages . Together, these studies show evidence that human SIRPA and pig CD47 can bind, although binding is not sufficient for phagocytic inhibition.…”
Section: Introductionmentioning
confidence: 96%